A methods engineering study on Jenny's Garments, Inc. - Deguito, Therese Sheila; Sabando, Luche; Valenzuela, Maria Sarah (Diliman, Quezon City College of Engineering, 1999)
A method study, time study and systems and procedures study was done on Jenny's Garments Inc., an outerwear (windbreakers, parkas) manufacturing company which caters to foreign based companies like JC Penney, Tommy Hilfiger, Nike, Charles River, etc. It was established in 1975 by the Juan family and in 1987 was sold to its present owners, the Lim family. The factory that was chosen for this study, which is located in Pasig, is responsible for 10 to 15 percent of the company's capacity and has the complete production process, from warehousing of the fabric to packaging of finished outerwears, compared to their satellite and sub-contracting factories. The sewing area of the chosen factory has four production lines. Since the Tommy Hilfiger production line has a one whole year production process, the researchers limited their study to this line. Having chosen the production line to be studied, the researchers formulated several objectives that will have to be met when the study is over. They wanted to able able to apply the different techniques learned in methods engineering, to learn the different processes in a garment manufacturing company and come up with ways of improving them, to find possible problem areas and make the necessary recommendations and to conduct method study and time study on the chosen production line. Observations were then made and data was gathered whenever the researchers had time off from their classes. By applying the different techniques learned in class, the researchers were able to identify three problem areas : bottleneck happening in the production line due to an unbalanced line; crisscrossing of work in process due to an inefficient layout; cluttering at the workplace due to insufficient racks and workstation trays for work in process; and no checklist form used. Several alternatives were then generated and the best was chosen to be the recommendation. For the problem regarding ineffective method of line balancing, the reseacherse recommend that the company rebalance the line by using the actual standard time calculated from the time study made. For the problem regarding inefficient layout, the researchers recommend that the company change the current layout of the Hilfiger line. For the problem regarding insufficient number of materials handling equipment, the researcheres suggest that the company add racks made of steel posts in the sewing area. For the problem regarding the checklist form, the researchers suggest that a mimeographing paper for the checklist be used.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Clothing trade; Systems analysis